Economic potential of formation of territories of rapid development in the Southern Russia: theoretical-methodical and instrumental approaches - N. A. Latushko (Новые технологии)
In the conditions of the current dynamics of economic development the policy of "focused" development of the territories, based on the creation of territories with a special status of economic development is changing the dominance of the policy of leveling the levels of social and economic development of the territories. Therefore, the purpose of this article is answering the question if the use of experience in implementing the TOP institutional format in the Far East in the territories of the subjects of the Southern Federal District is possible and appropriate.